On the semantics of the word bespredel in the literary Russian: О семантике слова беспредел в русском литературном языке - Barinova, Irina; Ovchinnikova, Irina (Przegląd Wschodnioeuropejski, 2020)
The paper presents the analysis of the semantic shifts in the lexical meaning of the lexeme bespredel (mayhem). The lexeme penetrates into the literary language from the jargon of criminals in 1990; its frequency dramatically increased in media and oral public communication. The shifts in its semantics were triggered by social transformations during Russian perestroika due to deconstruction of the socialist economy and political system. Bespredel in literary Russian acquired the meaning ‘extreme degree of chaos, when a person feels helplessness and vulnerability owing to violation of laws and rules’. According to the Russian national corpus, the word belongs to the media discourse while being rarely used in literature.